Groundwater and Sustainable Development Goals: Analysis of Interlinkages - Guppy, Lisa; Uyttendaele, Paula; Villholth, Karen G.; Smakhtin, Vladimir U. (2018)
Groundwater represents 97% of the world’s available freshwater resources and is extensively abstracted throughout the world. While abundant in a global context, it can only de developed to a certain extent without causing environmental impacts. Also, it is highly variable across the globe, and where it is heavily relied on, it is less renewable. Hence, it is critically important that this resource is managed sustainably. However, the Sustainable Development Goals (SDGs) of the 2030 Development Agenda do not, as a rule, account explicitly for the significant role that groundwater plays and will continue to play in sustainable development. This report aims to unpack and highlight this role through consistent analysis of the interlinkages between groundwater and the targets of the SDGs